The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ffj.3135
|View full text |Cite
|
Sign up to set email alerts
|

Predictive QSPR modelling for the olfactory threshold of a series of pyrazine derivatives

Abstract: Nowadays, much interest is shown in the prediction of different organoleptic properties of molecules for their prominent use in a variety of formulations and food products. Against this background, cheminformatics modelling was done in the present work for the development of predictive models for the olfactory threshold (log T) of a series of 74 pyrazine derivatives employing in silico techniques such as genetic function algorithm (GFA) and genetic partial least squares algorithm (G/PLS). Different categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(52 reference statements)
2
3
0
Order By: Relevance
“…Moreover, within the pyrazine series, both odour detection and recognition threshold values decreased with increasing number of alkyl substituents attached on the ring (2Ace3MePyz<2Ace3,5diMePyz<2,5diMePyz<5Et2,3diMePyz). This was consistent with other results revealing a strong influence of the degree of substitution on the pyrazine nucleus 48 and suggesting by quantitative structure–activity relationship (QSAR) a conformational and steric effect on the interaction with active sites of olfactory receptors 49–51 . Interestingly, the current findings also revealed that the presence of an acetyl functional group at 2‐position led to a significant decrease of both detection and recognition thresholds ( P ‐value <.05), whatever the nature of the heteroaromatic ring.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, within the pyrazine series, both odour detection and recognition threshold values decreased with increasing number of alkyl substituents attached on the ring (2Ace3MePyz<2Ace3,5diMePyz<2,5diMePyz<5Et2,3diMePyz). This was consistent with other results revealing a strong influence of the degree of substitution on the pyrazine nucleus 48 and suggesting by quantitative structure–activity relationship (QSAR) a conformational and steric effect on the interaction with active sites of olfactory receptors 49–51 . Interestingly, the current findings also revealed that the presence of an acetyl functional group at 2‐position led to a significant decrease of both detection and recognition thresholds ( P ‐value <.05), whatever the nature of the heteroaromatic ring.…”
Section: Resultssupporting
confidence: 92%
“…This was consistent with other results revealing a strong influence of the degree of substitution on the pyrazine nucleus 48 and suggesting by quantitative structure-activity relationship (QSAR) a conformational and steric effect on the interaction with active sites of olfactory receptors. [49][50][51] Interestingly, the current findings also revealed that the presence of an acetyl functional group at 2-position led to a significant decrease of both detection and recognition thresholds (P-value <.05), whatever the nature of the heteroaromatic ring. A number of N-heterocycles with acetyl function at position 2 have already been identified to present low odour thresholds.…”
Section: Data Processing and Statistical Analysissupporting
confidence: 57%
“…Among the four pyrazines studied, RDTs were continuously decreased with the increasing number of alkyl substituents attached to the ring, which was consistent with the result that both odor detection and recognition threshold values decreased in a spirit model medium (Goullet et al., 2023). Quantitative structure–activity relationship models of pyrazine‐based aroma compounds suggested a conformational and steric effect on the interaction with active sites of olfactory receptors (Buchbauer et al., 2000; Pal et al., 2013). Specifically, RDT of 2‐methylpyrazine was 63878.88 µg/L, about 0.52 times that of ODT, and RDT of 2,3,5,6‐tetramethylpyrazine was 1852.80 µg/L, with a one‐order magnitude difference between them.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies did not consider modeling OTP of wine components. Again, although there are some reports of QSPR modelling of OTP of some classes of odorants in general (for example, pyrazine derivatives, 15 aliphatic alcohols, 16 diverse air-borne volatile organic compounds 17 ), there has been no attempt so far to model specifically the odorant components of wine. Such attempt will definitely help to understand the dependence of the odor quality of different types of wines on their aroma constituents (for example, different manufacturing conditions may lead to different composition of odorant constituents in wine leading to a difference in odor quality).…”
Section: Introductionmentioning
confidence: 99%